How Radioactive Iodine Treatment Affects the Retina - Gürez, Ceren; Özen, Aynur; Ekmekçioğlu, Özgül (World Journal of Nuclear Medicine, 2023)
Objective The aim of this study was to quantitatively assess the macular and retinal nerve fiber layer thicknesses in patients with hyperthyroidism and thyroid cancer undergoing radioactive iodine (RAI) therapy.Study Design This prospective study was conducted in accordance with the principles of the Declaration of Helsinki and approved by the Bagcilar Training and Research Hospital Clinical Research Ethics Committee. Written informed consent was obtained from the patients following a detailed explanation of the study objectives and protocol. Patient selection was randomized. Patients scheduled for RAI treatment in the Nuclear Medicine Clinic were referred to the ophthalmology clinic, respectively. Patients without additional ocular pathology were included in the study.Methods All patients had received RAI therapy using Iodine-131 for hyperthyroidism or thyroid cancer. A complete ophthalmological examination and measurement of macular and retinal nerve fiber layer thickness using optical coherence tomography were performed on all patients before and at the first and sixth months and in first year after RAI treatment. The results were prospectively evaluated.Results The study included 80 eyes of 40 patients. The hyperthyroid group was group 1, and the thyroid cancer group was group 2. There were 25 patients in group 1 and 15 patients in group 2. The mean age was 43.76 ± 11.85 years (range: 22–65 years) in group 1 and 39.87 ± 9.13 years (range: 30–58 years) in group 2. There was no significant difference between the two groups regarding age and sex (p > 0.05). In both groups, no significant difference was found in the macular thickness and retinal nerve fiber layer thicknesses values obtained in both eyes before and after the RAI treatment.Conclusion As a result of our study, we observed that RAI intake did not harm the retinal layer.
Keywords: Macula; nerve fiber layer; radioactive iodine; thyroid cancer; hyperthyroidism